Uso de computação algebrica aplicada ao ensino de Ciências - SILVA, Joedila Felipe da (2024)
This work, qualitative and theoretical, deals with the Use of Algebraic Computing Applied to Science Teaching with the use of Maxima software as an effective technological tool in Science Teaching. The present work aims to introduce basic notions and commands of the Maxima software to assist and stimulate students and teachers in the classroom and apply them in various contexts of science teaching. The course work is presented in book format, which was organized as follows: introduction to the software, installation of the program on the computer and/or cell phone and notions of how to handle it; understanding of the use of basic functions, graphic manipulations and animations in GIF format of the referred tool; and the applicability of the tool in science teaching, highlighting practical examples of application of Maxima in Science/Physics teaching activities, in order to solve some Physics problems, addressing issues such as Newton's kinematics and dynamics, position, average velocity, force, acceleration, work and energy, demonstrating the practicality and effectiveness of the solutions, as a way to arouse the interest of students and teachers interested in understanding the logical sequence of AC Algebraic Computation applied to Science teaching. It is concluded that the use of the Maxima software in the teaching of Science/Physics is of great help in the construction of knowledge since it improves the understanding of technological knowledge applied to the teaching of science and facilitates academic learning.